2011
DOI: 10.1139/e10-107
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary response to orogenic exhumation in the northern Rocky Mountain Basin and Range province, Flint Creek basin, west-central Montana

Abstract: Middle Eocene through Upper Miocene sedimentary and volcanic rocks of the Flint Creek basin in western Montana accumulated during a period of significant paleoclimatic change and extension across the northern Rocky Mountain Basin and Range province. Gravity modelling, borehole data, and geologic mapping from the Flint Creek basin indicate that subsidence was focused along an extensionally reactivated Sevier thrust fault, which accommodated up to 800 m of basin fill while relaying stress between the dextral tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…Moreover, the magnitude of extensional deformation decreased eastward across the eastern Idaho and southwestern Montana region, becoming progressively more obscure beyond the eastern limit of the study area. Thus, the effect of Eocene extension upon relief and accommodation may have been signifi cantly less within our study area than suggested for westward locations (e.g., Portner et al, 2011). Therefore, we submit that during the latest Cretaceous and early Paleogene, fl uvial incision was a primary mechanism for forming an interconnected network of large-scale paleovalleys that served as primary depocenters (basins) throughout Cenozoic time.…”
Section: Reconciling Extension Uplift and Erosionmentioning
confidence: 75%
“…Moreover, the magnitude of extensional deformation decreased eastward across the eastern Idaho and southwestern Montana region, becoming progressively more obscure beyond the eastern limit of the study area. Thus, the effect of Eocene extension upon relief and accommodation may have been signifi cantly less within our study area than suggested for westward locations (e.g., Portner et al, 2011). Therefore, we submit that during the latest Cretaceous and early Paleogene, fl uvial incision was a primary mechanism for forming an interconnected network of large-scale paleovalleys that served as primary depocenters (basins) throughout Cenozoic time.…”
Section: Reconciling Extension Uplift and Erosionmentioning
confidence: 75%
“…The northern footwall of the AMCC, proximal to the Pioneer District placers, is composed of folded Mesoproterozoic-Mesozoic metasedimentary and sedimentary rocks that have been intruded by several granite and granodiorite plutons (Fig. 2;Emmons and Calkins, 1913;Grice, 2006;Portner et al, 2011). The dominant plutons include the 69-60 Ma Royal stock and the 65 Ma two-mica (muscovite and biotite) Mount Powell batholith (Fig.…”
Section: Geologic Settingmentioning
confidence: 99%
“…Many of the strata now exposed in the hanging wall of the AMCC are interpreted to have been deposited in an Eocene-Oligocene supradetachment basin (the "Flint Creek Basin") that developed contemporaneous with slip along the Anaconda detachment (Janecke et al, 2005;Stroup et al, 2008). The late Oligocene-early Miocene Cabbage Patch Formation and mid-Miocene Squaw Gulch conglomerate beds were deposited atop the hanging wall of the Anaconda detachment and have a combined thickness of ~800 m, constituting most of the Flint Creek Basin fill (Fields et al, 1985;Loen, 1986;Stroup et al, 2008;Portner et al, 2011). It has been hypothesized that the Cabbage Patch Formation and Squaw Gulch beds were the original depositional units of the Pioneer District placer deposits prior to subsequent glacial transport and redeposition as fluvial placers in the Pleistocene (Loen, 1986).…”
Section: Geologic Settingmentioning
confidence: 99%
See 2 more Smart Citations